Mechanistic insights into histone deposition and nucleosome assembly by the chromatin assembly factor-1. Issue 19 (18th September 2018) - Sauer, Paul V; Gu, Yajie; Liu, Wallace H; Mattiroli, Francesca; Panne, Daniel; Luger, Karolin; Churchill, Mair EA
Abstract: Eukaryotic chromatin is a highly dynamic structure with essential roles in virtually all DNA-dependent cellular processes. Nucleosomes are a barrier to DNA access, and during DNA replication, they are disassembled ahead of the replication machinery (the replisome) and reassembled following its passage. The Histone chaperone C hromatin A ssembly F actor-1 (CAF-1) interacts with the replisome and deposits H3–H4 directly onto newly synthesized DNA. Therefore, CAF-1 is important for the establishment and propagation of chromatin structure. The molecular mechanism by which CAF-1 mediates H3–H4 deposition has remained unclear. However, recent studies have revealed new insights into the architecture and stoichiometry of the trimeric CAF-1 complex and how it interacts with and deposits H3–H4 onto substrate DNA. The CAF-1 trimer binds to a single H3–H4 dimer, which induces a conformational rearrangement in CAF-1 promoting its interaction with substrate DNA. Two CAF-1H3–H4 complexes co-associate on nucleosome-free DNA depositing (H3–H4)2 tetramers in the first step of nucleosome assembly. Here, we review the progress made in our understanding of CAF-1 structure, mechanism of action, and how CAF-1 contributes to chromatin dynamics during DNA replication.